Dose Calculation and Measurement from B¹⁰(n, α)Li⁷ Reaction Using Filtered Neutron Beam at Nuclear Research Institute - Trinh Thi , Tu Anh; Nguyen, Danh Hung; Pham, Dang Quyet; Pham, Ngoc Son (Nuclear Science and Technology, 2018)
In this research, dose calculation and measurement from B10 (n, α) Li7 reaction using filtered neutron beam at the Nuclear Research Institute have been reported. Calculation was carried out by Monte Carlo method using MCNP5 code. Neutron activation technique using vanadium foil was employed to determine neutron flux at various positions in phantom from which neutron dose has been calculated using conversion factor. These calculations are basics for the dose determination research of the Boron Neutron Capture Therapy (BNCT) in Vietnam.